Derivation of ancient Egyptian faience core and glaze materials - Stocks, Denys A.
An essential ingredient of the lovely blues in ancient Egyptian materials Ñ faience, glazes, frits Ñ is copper. How did the knowledge of that copper use arise? There is a telling congruence with Egyptian techniques in drilling stone artefacts, and the characteristics of the powder drilled out as waste.